Cointegration Indeks Harga Saham Gabungan dan Jakarta Islamic Index Periode 2015-2019 - Ahmad Hilmy; Yuyun Isbanah (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
Examines co-movement between IHSG and JII that represent conventional stock indices and shariah stock indices in the 2015-2019 period was to be the focus on this paper. Co-movement studies have benefits for investor to have diversification opportunities on their portfolio investments asset and their decision making in the future. This study examines how the two different assets characteristic move in long term relationships and short term relationships. The sample data have gathered from the monthly closing price in five years range. Any method that used in this study using The Augmented Dickey-Fuller Test for stationarity test, Johansen Test for Cointegration, Error Correction Model for a short-run relationship, and Granger causality test for finding any causality between two variables. The data sample using a non-probability sampling technique. This study reveals evidence if two indices variables not co-movement in each other especially not cointegrating and not have any causality between them in 2015-2019 period. This findings also have implied on investor benefit for investment decision making and better policy decision making.